Linear Elastic Analyses of Masonry Walls - Sayın, Erkut; Calayır, Yusuf (Fırat University, 2018)
Masonry structures are commonly used in many countries. Load bearing masonry walls are the most important structural element in the masonry structures. In this study, a computer program was written in MATLAB for linear elastic analyses of masonry walls. In addition, a mesh program which meshes the wall as two dimensional model was written in MATLAB. These models were constituted with macro modelling approach. Three different load cases were applied to two dimensional masonry model with opening. The obtained results from the linear elastic analysis were compared with ANSYS software results.
Keywords: Engineering; Mühendislik